Analisis dan Rekontruksi Lembar Kerja Peserta Didik Pada Konsep Sistem Pencernaan Makanan di SMA: (Analysis and Reconstruction of Student Worksheets On Concept Digestive System Food In Senior High School) - Deri Adiyanto; Sri Anggraeni; Bambang Supriatno (BIODIK, 2021)
Student worksheets as guide for implementation of the practicum process to improve the skills of students. but, in reality this is not case. This study aims to analyse and describe aspesct of relevance, curriculum, practical and knowledge construction on student worksheets used in second from the curriculum 1984 to curricullum 2013 revision as well as to reconstructs the LKPD components. The research method is descriptive qualitative ANCOR model. The research samples was take by using purposive sampling technique with 7 LKPD. The research instrument used was the analysis of relevance, competence, practically and knowledge construction which was adapted from Novak & Gowin (1984). The results showed that the LKPD on the concept of the digestive system in the 1994, 2006, 2013, 2013 revision curriculum had several components that had to be reconstructed, besides that the development of LKPD content did not change according to curriculum development, this practicum had been carried out in junior high schools. Therefore, it is necessary to improve LKPD in the concept of the food digestive system. The components that are repaired: Activity objectives, theoretical basis, tools and materials, work steps, data recording and practical question, this improvement is expected to provide an understanding in accordance with the demands of the current curriculum, namely the 2013 curiculum, providing a more meaningful practicum, besides that, students are able to increase minds on and hands on abilities in practicum activities to face the era of industrial revolution 4.0. Abstrak. Lembar Kerja Peserta Didik sebagai penuntun proses pelaksanaan praktikum untuk meningkatkan keterampilan peserta didik. Namun pada kenyataanya tidak demikian. Penelitian ini bertujuan untuk menganalisian mendeskripsikan aspek relevansi, kurikulum, praktikal dan konstruksi pengetahuan pada lembar kerja peserta didik yang digunakan di sekolah dari kurikulum tahun 1984 sampai erta merekontruksi komponen LKPD. Metode penelitian adalah deskriptif kualitatif model ANCOR. Pengambilan sampel penelitian dilakukan dengan teknik purposive sampling LKPD berjumlah 7 buah. Instrumen penelitian yang digunakan yaitu analisis relevansi, kompetensi, praktikal dan konstruksi pengetahuan yang diadaptasi dari Novak & Gowin (1984). Hasil penelitian menunjukkan LKPD pada konsep sistem pencernaan pada kurikulum tahun 1994, 2006, 2013, 2013 revisi memiliki beberapa komponen yang harus direkontruksi, selain itu perkembangan konten LKPD tidak berubah sesuai perkembangan kurikulum, praktikum tersebut pernah dilakukan di SMP. Oleh karena itu diperlukan perbaikan LKPD pada konsep sistem pencernaan makanan. Adapun komponen yang diperbaiki antara lain : tujuan kegiatan, dasar teori, alat dan bahan, langkah kerja, perekaman data dan pertanyaan praktikan, perbaikan ini diharapkan memberikan pemahaman yang sesuai dengan kurikulum 2013 revisi, memberikan praktikum yang lebih bermakna, selain itu supaya peserta didik mampu meningkatkan kemampuan minds on dan hands on dalam kegiatan praktikum untuk menghadapi era revolusi industri 4.0.